2013
DOI: 10.1016/j.molonc.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Claudin‐2 is an independent negative prognostic factor in breast cancer and specifically predicts early liver recurrences

Abstract: Keywords:Breast cancer Liver metastasis Claudin-2 Prognostic biomarker A B S T R A C TBackground: Predicting any future metastatic site of early-stage breast cancer is important as it significantly influences the prognosis of advanced disease. This study aimed at investigating the potential of claudin-2, over-expressed in breast cancer liver metastases, as a biomarker for predicting liver metastatic propensity in primary breast cancer.Methods: Claudin-2 expression was analyzed in two independent cohorts. Cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 40 publications
8
61
0
Order By: Relevance
“…By using experimental mouse models and a limited series of clinical metastatic biopsies, genes associated with the propensity of breast cancer relapse to the bone (16), lung (17,18), and brain (19) have been published. Furthermore, we (7) and others (20,21) have shown an association between claudin-2 expression and liver recurrence. However, because experimental mouse models incompletely capture the relevant genetic complexity of tumor progression within the human host, studies using patientderived biopsies from metastases may reveal additional clinically relevant site-specific attributes to complement and/or validate these preliminary reports.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…By using experimental mouse models and a limited series of clinical metastatic biopsies, genes associated with the propensity of breast cancer relapse to the bone (16), lung (17,18), and brain (19) have been published. Furthermore, we (7) and others (20,21) have shown an association between claudin-2 expression and liver recurrence. However, because experimental mouse models incompletely capture the relevant genetic complexity of tumor progression within the human host, studies using patientderived biopsies from metastases may reveal additional clinically relevant site-specific attributes to complement and/or validate these preliminary reports.…”
Section: Introductionsupporting
confidence: 55%
“…Because liver relapse is indicative of inferior postrecurrence survival, there is a need for more specific and independent biomarkers to identify patients at risk. Recently, we demonstrated that CLDN2, which is significantly upregulated in liver metastases, is an independent prognostic factor for early liver recurrence in breast cancer (7). Here, we show that downregulation of various genes involved in cell adhesion is characteristic of liver metastases.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Four previously published microarray datasets were used in our study. GSE46141 dataset was used to identify distant metastasis-specific genes, it is derived from fine-needle aspiration biopsies of breast cancer metastases from different anatomical sites including 23 distant metastases (18 liver, 4 bone, 1 ascite) and 67 local metastases (breast, regional lymph node or skin) [7]. The expression, annotation and clinical data of GSE46141 were downloaded from Gene Expression Omnibus (GEO) database.…”
Section: Methodsmentioning
confidence: 99%
“…Claudin-2 plays a key role in mediating the interaction between hepatocytes and cancer cells promoting the activation of metastatic signaling pathways. Indeed, Claudin-2 expression is considered a poor prognosis factor that mediates breast cancer relapse to the liver [24,25].…”
mentioning
confidence: 99%